The immunogenetics of LGI1- and CASPR2-antibody encephalitis: towards aetiology - Binks, S (2022)
Autoimmune neurology is a rapidly expanding scientific and clinical field encompassing a range of conditions caused by autoantibodies to surface neuronal proteins. These entities, which have access to their target proteins in vivo, can disrupt neurological functions. One classically associated clinical syndrome is limbic encephalitis (LE), characterised by seizures, cognitive impairment and personality change. The most frequent autoantibodies found in LE are to leucine-rich glioma-inactivated 1 (LGI1), its close biological partner contactin-associated protein 2 (CASPR2), and the N-methyl D-aspartate receptor (NMDAR). While the aetiological link between these antibodies and distinct disease phenotypes is clear, mechanisms of causation remain to be determined. These are of great fundamental biological interest and represent the most common question posed by patients and their families. Work leading up to this DPhil identified a strong major histocompatibility complex (MHC – also known as human leucocyte antigen or HLA in Homo sapiens) link in both LGI1-antibody and CASPR2-antibody disease, with ~90% of LGI1-antibody patients carrying HLA-DRB1*07:01, and HLA-DRB1*11:01 in ~50% with CASPR2-antibodies. Nevertheless, these HLA alleles are not sufficient to cause disease since they are carried by ~25% and ~10% of the healthy population respectively. Hence, additional genetic or environmental factors are likely important in disease pathophysiology. The introduction (Chapter 1) to this thesis outlines current understanding of molecular, genetic and phenotypic aspects of antibody-mediated encephalitis, with an emphasis on LGI1-, CASPR2- and NMDAR-antibody disease. Disease models are discussed, including spontaneously-arising forms in non-human mammals, notably LGI1-antibody encephalitis (LGI1-Ab-E) in pet cats. Chapter 2 analyses deep clinical phenotyping of cognitive, neuropsychiatric and quality-of-life (QoL) outcomes in 60 patients with LGI1-antibodies, alongside serological findings. The two subsequent chapters describe contrasting methods used to explore possible additional genetic factors: Chapter 3 applies the genome-wide association study (GWAS) approach to a discovery and validation cohort of LGI1-Ab-E, and, in Chapter 4, targeted next-generation sequencing (NGS) is employed in a rationally-designed neuroscience panel in 96 individuals with LG1, CASPR2, LGI1 and CASPR2, or NMDAR-antibodies to identify common and rare alleles. To evaluate parallels between felines and their human counterparts, Chapter 5 describes clinical features of the largest cohort assembled to date of domestic cats with LGI1-Ab-E. Finally, Chapter 6 synthesizes the different research strands of this thesis and identifies future work that is in progress or planned to take place, focussing on expanding genetic methodologies and targets that could deliver insights into disease mechanisms.